Inhibition of Mammalian Target of Rapamycin (mTOR) Signaling in the Insular Cortex Alleviates Neuropathic Pain after Peripheral Nerve Injury - Kwon, Minjee; Han, Jeongsoo; Kim, Un Jeng; Cha, Myeounghoon; Um, Sun Woo; Bai, Sun Joon; Hong, Seong-Karp; Lee, Bae Hwan (Frontiers in Molecular Neuroscience, 2017)
Injury of peripheral nerves can trigger neuropathic pain, producing allodynia and hyperalgesia via peripheral and central sensitization. Recent studies have focused on the role of the insular cortex (IC) in neuropathic pain. Because the IC is thought to store pain-related memories, translational regulation in this structure may reveal novel targets for controlling chronic pain. Signaling via mammalian target of rapamycin (mTOR), which is known to control mRNA translation and influence synaptic plasticity, has been studied at the spinal level in neuropathic pain, but its role in the IC under these conditions remains elusive. Therefore, this study was conducted to determine the role of mTOR signaling in neuropathic pain and to assess the potential therapeutic effects of rapamycin, an inhibitor of mTORC1, in the IC of rats with neuropathic pain. Mechanical allodynia was assessed in adult male Sprague-Dawley rats after neuropathic surgery and following microinjections of rapamycin into the IC on postoperative days 3 and 7. Optical recording was conducted to observe the neural responses of the IC to peripheral stimulation. Rapamycin reduced mechanical allodynia and downregulated the expression of postsynaptic density protein 95, decreased neural excitability in the IC, thereby inhibiting neuropathic pain-induced synaptic plasticity. These findings suggest that mTOR signaling in the IC may be a critical molecular mechanism modulating neuropathic pain.